141 Sickle cell disease and physical activity: Is it safe?. (29th October 2021) - Corvalan Cifuentes, Melissa-Zoraya; Pastore, Yves D; Nguyen, Thanh-Diem; Bérubé, Denis; Dahdah, Nagib
Abstract: Primary Subject area: Hematology and Oncology - Paediatric Background: Though physical activity (PA) is beneficial for healthy individuals and for those with chronic disease, its impact on sickle cell disease (SCD) children remains poorly studied. Moreover, patients may refrain from PA given a perceived fear of SCD complications. Objectives: 1) Evaluate whether SCD children engage differently in PA compared to their peers. 2) Evaluate the cardiopulmonary impact of PA in a group of SCD patients. Design/Methods: Prior to the COVID-19 pandemic, SCD patients aged 8-17 years old consented to answer a PA questionnaire (PAQ) and have their school peers answer the same PAQ. PAQ, a well-described surrogate marker of PA, is a standardized questionnaire evaluating PA during the last 7 days. Patients and their peers were approached only during the school year. A set of HbSS patients were invited to participate in a supervised exercise test including pre- and post-effort PFT, echocardiography, EKG, measurement of troponins and NT-proBNP and a methacholine challenge to evaluate exercise-induced bronchial hyperreactivity. T-test was used as statistical analysis, using SPSS V24. The study received IRB approval. Results: Questionnaires from 25 SCD children (13 SS and 12 SC) were compared with 36 matched-school peers. SCD patients were overall less active (p=0.04). While their level of activity was similar at school, SCD patients were overall less active after school (p=0.028), in the evening (p=0.008) and weekends (p=0.049). While the difference was significant for both SS and SC patients, SS were less active than SC, although this difference was statistically not significant. Five HbSS patients on HU were subjected to an exercise test. There were no statistical differences in the pre- and post-PA evaluations including measurements of troponin, NT-proBNP and functional testing. None of them had exercise-induced hyperreactivity. Conclusion: Overall, SCD patients are less active than their peers, mostly outside of school. The absence of cardiopulmonary modifications during PA is reassuring, although our study was limited to 5 HbSS patients on HU. Whether HU has a protective role cannot be excluded. Our results encourage us to further evaluate PA interventions outside of school in SCD patients. Interventional studies evaluating the risk-benefit ratio of PA in SCD children are further needed.